Ashaykh Mahmud bin Bakr Ali Al-bukhari Al-Kalabadhi. His Life and Works( A specialized Study to His Book Daw-us-Siraj fi llm il - Fraid)("الشيخ محمود بن بكر البخاري الكلاباذي: حياته وآثاره (دراسة متخصّصة لكتابه " ضوءالسراج في علم الفرائض - Dr.Asma Ali (الإيضاح, 2019)
Ashaykh Mahmūd bin Abī Bakr bin Abīulala bin Alī Al-bukhārī Al-kalābādhī is one of scholars of Mirāth. He was born in 644 A.H. and died in 700 A.H. He was a man of eminence in Central Asia. He visited many metropolitan cities across the world to get knowledge. During his foreign visits, he contacted great scholars of Islamic sciences. Similarly, thousands of students used to attend his lectures. Allāmah Kalābādhī was a man of letters. He wrote many books. Famous of them are: Ḥall ul Frāi Fī Sharah Naẓm Assirājiyah, Ḍaw us Sirāj Fī Sharah Assirājiyah, Mushtabeh un Nasab Fī Asmā ur Rijāl, Mujamush Shuyūkh, Al Minhāj Al Muntakhab.